The Prevalence of Domestic Violence and Its Association with Gestational Hypertension in Pregnant women - Ebrahimi1, Elham; Karimian2, Zahra; Khayati Motlagh Bonab1, Shiva; Bolbolhaghighi3, Nahid; Beigi4, Jamal; Saeedi5, Roghaieh; Tavakoli1, Zohreh (Shahroud Journal of Medical Sciences, 2017)
Background: Violence against women forms one of the most brutal consequences of the economic, social, political, and cultural inequalities that exist between men and women. Violence can lead to less participation in social activities, unhappiness, emotional distress, and increased risks of maternal medical conditions such as hypertensive disorders of pregnancy, which are leading causes of maternal mortality worldwide.Methods: We conducted a case–control study at Shahid-Beheshti hospital in Maragheh, Azarbaijan, Iran. About 110 women with pregnancy revealed hypertension and proteinuria (i.e., preeclampsia), and 451 normotensive women were interviewed to identify the prevalence of domestic violence. Information concerning women’s exposure to physical, emotional, and sexual violence during pregnancy was collected during personal interviews conducted after delivery and while patients were in hospital. Odds ratios (OR) and 95% confidence intervals (CI) were estimated from logistic regression models.Results: The prevalence of IPV was 56.1% among cases and 24.3% among controls. Women with some exposure to IPV during pregnancy revealed a 2.07-fold increased risk of preeclampsia compared to those who were not exposed to IPV (OR=2.07; 95% CI: 1.5–3.02). The association between IPV and preeclampsia was strengthened slightly after adjusting for maternal age, parity and pre-pregnancy adiposity (OR=2.43; 95% CI: 1.7–3.24).Conclusions: Violence as a social issue is affected by social and cultural diferences .So that ,empowering of women and adolscents as a group that by knowing the factors that lead to the violence and its probable effects ,we can prevent it.